SPACE LEXICALIZATION IN COMPOSITIONS BY INDONESIAN EFL LEARNERS: TOWARD NEAR-NATIVE STYLE - A. Effendi Kadarisman (Fakultas Sastra Universitas Negeri Malang, 2011)
This research intends to find out whether or not Indonesian EFL learners are aware of the presence of “space” and lexicalize it in their English compositions. It takes 21 seventh-semester English Department students as research subjects. They are given story pictures and asked to write a narrative. The resulting 21 EFL narratives are measured against a native-speaker narrative model in terms of “spatial words” (prepositions and adverbial particles), producing the following comparisons: 6.6% : 7.2% in total, 78.2% : 85.7% used dynamically, 95.5% : 100% used obligato-rily, and 19.2% : 28.6% used in phrasal verbs. This means that Indonesian EFL learners are sensitive enough to “space” and know how to lexicalize it in their com- positions. Theoretically, their sensitivity to “space” implies that while learning Eng- lish they have undergone some cognitive restructuring; and practically, EFL learners who wish to acquire near-native style in writing should be competent in space lexi- calization.